Swiss wine market report - Spahni, Pierre (Woodhead Publishing, 1998)
The Swiss wine industry is waking up to a new challenge: to raise the competitiveness of its wines, which has been eroded by the general strength of the country's currency during the first half of the 1990s and is becoming ever more evident as the liberalisation of the country's trade regime is taking hold. This report brings together material on the vital issues shaping the future of the Swiss wine market. After a brief look at the country's socio-economic situation, consumption patterns are reviewed. The market for reds and for whites is then examined. Much of the emphasis is laid on.